The world according to iTunes: mapping urban networks of music production - Allan Watson (2012)
This paper explores the global urban networks formed through creative project ecologies within the global recorded music industry. The paper presents a social network analysis in which recorded music albums are viewed as temporary market-based projects that bring together teams of skilled creative individuals in recording studios across the globe. New tools and techniques for networking studios in geographically distant locations give mobile musical creatives the ability to coordinate musical recordings on a global scale, resulting in new relational geographies of music production. The analysis assesses the connectedness of cities and determines the centrality and power of cities within networks of production for the UK and US digital music markets. The main finding is the dominance of an Anglophone triad of global cities consisting of New York, Los Angeles, and London, which mediate global networks of musical recording.